Failed repeated thrombolysis requiring left ventricular assist device pump exchange. Issue 6 (22nd August 2012) - Tang, Gilbert H.L.; Kim, Michael C.; Pinney, Sean P.; Anyanwu, Anelechi C.
<x xml:space="preserve">Abstract</x> A 51‐year‐old male with untreated hepatitis C infection, cirrhosis, and dilated cardiomyopathy with a HeartMate II LVAD presented with right heart failure and cardiogenic shock, INR of 7, hemolysis, and renal failure. Acute LVAD thrombosis was suspected. Alteplase was injected into the inflow cannula of the LVAD with little effect. Intravenous alteplase was given but failed to restore an adequate pump output, resulting in the need for emergency pump exchange. The patient had an uncomplicated postoperative recovery and was discharged uneventfully. Inspection of the pump identified a thrombus wedged between the spines of the impeller. Our case highlights the challenges in managing pump thrombosis which is often resistant to thrombolysis and may instead rely upon prompt surgical intervention to be resolved. © 2012 Wiley Periodicals, Inc.